Mobility for learners and staff higher education students and staff mobility inter-institutional agreement 2014-2021 between programme countries Universidade Lusíada de Lisboa and Universitat Autònoma de Barcelona - Universidade Lusíada de Lisboa (2016)
- Cooperate within the Erasmus-programme in the frame of the Eu-Programme Lifelong Learning. - Subject area: Tourism and catering, Management.